The New Life : Jewish Students of Postwar Germany - Varon, Jeremy (Book collections on Project MUSE., 2014)
Examines the experiences of Jewish university students, survivors of the Holocaust who either remained as displaced persons in Germany or fled eastern Europe to the parts of Germany occupied by western powers as refugees--